Candida albicans isolated from urine: Phenotypic and molecular identification, virulence factors and antifungal susceptibility - Wiebusch, Laura; Almeida-Apolonio, Adriana Araujo de; Carbonera Rodrigues, Luana Mireli; Bicudo, Bruna de Paula; Santos Silva, Danielly Beraldo dos [UNESP]; Lonchiati, Danielle Ferreira; Araujo, Renata Pires de; Grisolia, Alexeia Barufatti; Pires de Oliveira, Kelly Mari (Wolters Kluwer Medknow Publications, 2017)
Objective: To isolate Candida albicans (C. albicans) from the urine of hospitalized patients and assess the virulence factors and antifungal susceptibility profiles of the isolates. Methods: Yeasts were identified using the chromogenic medium CHROMagar (TM), the VITEK (R) 2 system, hypertonic Sabouraud broth, tobacco agar, polymerase chain reaction, and DNA sequencing. The evaluated virulence factors were proteinase production, phospholipase production, and biofilm production on polystyrene. The broth micro-dilution technique was used to determine the minimum inhibitory concentration. Results: All yeasts isolated from urine were identified as C. albicans using both classical and molecular methods. Although 91.3% of the isolates showed no phospholipase activity, 56.5% showed strong proteinase activity and 91.7% produced biofilm. All microorganisms were sensitive to fluconazole, voriconazole and amphotericin B, but 56.5% of the yeasts showed resistance to itraconazole. Conclusions: C. albicans isolates from urine have a high capacity for virulence and can be associated with infectious processes. Furthermore, the high percentage of isolates resistant to itraconazole is important because this antifungal agent is commonly used to treat fungal infections in the hospital environment.